2x-(3x+6)=4x-46

Simple and best practice solution for 2x-(3x+6)=4x-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(3x+6)=4x-46 equation:


Simplifying
2x + -1(3x + 6) = 4x + -46

Reorder the terms:
2x + -1(6 + 3x) = 4x + -46
2x + (6 * -1 + 3x * -1) = 4x + -46
2x + (-6 + -3x) = 4x + -46

Reorder the terms:
-6 + 2x + -3x = 4x + -46

Combine like terms: 2x + -3x = -1x
-6 + -1x = 4x + -46

Reorder the terms:
-6 + -1x = -46 + 4x

Solving
-6 + -1x = -46 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-6 + -1x + -4x = -46 + 4x + -4x

Combine like terms: -1x + -4x = -5x
-6 + -5x = -46 + 4x + -4x

Combine like terms: 4x + -4x = 0
-6 + -5x = -46 + 0
-6 + -5x = -46

Add '6' to each side of the equation.
-6 + 6 + -5x = -46 + 6

Combine like terms: -6 + 6 = 0
0 + -5x = -46 + 6
-5x = -46 + 6

Combine like terms: -46 + 6 = -40
-5x = -40

Divide each side by '-5'.
x = 8

Simplifying
x = 8

See similar equations:

| 10^3•10^-5•10^10/10^6 | | 2y-5x=-9 | | 6x-1=2x+16 | | 3(78-20)=n | | 3807=47(p+20) | | 5n-2=n+2 | | 350=14(3x+7) | | 5/8a=25 | | 12j+15=-20+5j | | 80=8(2x-4) | | C=3.14(46) | | Log2/y | | 5(x+14)=140 | | 4x^3-8x^2-6x+4=0 | | C=3.14(19) | | 36345.8=8.6(36504.9n) | | 160=20(2x-10) | | 8x+-3.8=-8x+-7 | | F(500)=1.5x+300 | | 5x+5=2X+4 | | 160=24(2x-5) | | (3x^2-14x-5)/(x-5) | | C=2(3.14)(21) | | 1440=36(3x+10) | | 10x+6=166 | | F(200)=1.5x+300 | | C=3.14(26) | | 9p+7p=7 | | 5(7-x)=65 | | 1260=35(3x+9) | | 3(x-1)/3(1-x) | | (sin(x))=1-2(sin^2(x)) |

Equations solver categories